2021
DOI: 10.1093/elt/ccab082
|View full text |Cite
|
Sign up to set email alerts
|

English medium higher education in China: challenges and ELT support

Abstract: This mixed-methods study explores the language-related difficulties and ELT support offered in English-medium programmes at eight universities in China. Data included a student questionnaire (n = 394) measuring the difficulties of 45 academic tasks, organized around the four skills of reading, writing, listening, and speaking. Results revealed students faced the largest difficulties with productive skills, especially writing. To explore structural language support for overcoming such challenges, fieldwork inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…As noted by Nguyen et al (2017) , implementing EMI in educational environments may entail some important challenges and opportunities for both teachers and students, which need to be discovered. In this respect, several researchers have explored the problems and benefits of implementing EMI in different academic contexts, notably higher education contexts (e.g., Goodman, 2014 ; Hu, 2019 ; Phuong and Nguyen, 2019 ; Yang et al, 2019 ; Aizawa and McKinley, 2020 ; Drljaca and Vodopija-Krstanovic, 2020 ; Pun and Thomas, 2020 ; Toh, 2020 ; Derakhshan et al, 2021 ; Kamaşak et al, 2021 ; Pun and Jin, 2021 ; Soruç et al, 2021 ; Ter-Vardanyan, 2021 ; Zare and Derakhshan, 2021 ; Jones et al, 2022 ; Zhou et al, 2022 , among others). As to the challenges of EMI classes, Yang et al (2019) , for instance, examined the challenges of implementing EMI in medical courses in China.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted by Nguyen et al (2017) , implementing EMI in educational environments may entail some important challenges and opportunities for both teachers and students, which need to be discovered. In this respect, several researchers have explored the problems and benefits of implementing EMI in different academic contexts, notably higher education contexts (e.g., Goodman, 2014 ; Hu, 2019 ; Phuong and Nguyen, 2019 ; Yang et al, 2019 ; Aizawa and McKinley, 2020 ; Drljaca and Vodopija-Krstanovic, 2020 ; Pun and Thomas, 2020 ; Toh, 2020 ; Derakhshan et al, 2021 ; Kamaşak et al, 2021 ; Pun and Jin, 2021 ; Soruç et al, 2021 ; Ter-Vardanyan, 2021 ; Zare and Derakhshan, 2021 ; Jones et al, 2022 ; Zhou et al, 2022 , among others). As to the challenges of EMI classes, Yang et al (2019) , for instance, examined the challenges of implementing EMI in medical courses in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given that understanding the challenges and opportunities of EMI courses improves their quality ( Walkinshaw et al, 2017 ; Wei et al, 2017 ), many academics and researchers worldwide have investigated the advantages and disadvantages of implementing EMI in higher educational contexts (e.g., Bradford, 2016 ; Martínez, 2016 ; Cankaya, 2017 ; Kim, 2017 ; Kim et al, 2018 ; Phuong and Nguyen, 2019 ; Aizawa and McKinley, 2020 ; Toh, 2020 ; Diezmas and Barrera, 2021 ; Kamaşak et al, 2021 ; Soruç et al, 2021 ; Ter-Vardanyan, 2021 ; Wang and Derakhshan, 2023 , to cite a few). Moreover, some scholars have particularly scrutinized the advantages and disadvantages of implementing EMI in Chinese academic settings (e.g., Yang et al, 2019 ; Pun and Thomas, 2020 ; Pun and Jin, 2021 ; Zhou et al, 2022 , among others). However, to the best of the scholars’ knowledge, no empirical study has been undertaken to identify the opportunities and challenges of executing EMI in Chinese art and music classes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To make full use of linguistic and cultural diversity, alternative multilingual models of EMI have been proposed in which English functions in tandem with other languages instead of replacing them (Barnard & McLellan, 2014). Zhou et al (2022) claimed that when multilingual students have not yet acquired complex disciplinary discourses, they should be allowed to deploy their full linguistic repertoire, which includes their L1. More importantly, including L1 is less about language creativity, but more about systematically leveraging L1 to help students comprehend disciplinary complexity.…”
Section: Conceptualizing Emi In the Multilingual Turnmentioning
confidence: 99%
“…Students felt that, in addition to the EAP courses, their content lecturers should help them with language-related problems. Zhou et al (2022) surveyed students and staff in eight Chinese universities and found that concurrent language courses, run by an independent language centre, was the prevalent offer, followed by self-access study and preparatory language courses. However, the researchers did find 'grassroots efforts of language scaffolding initiated by content teachers' (p. 8).…”
Section: Student Support In Emi and Eapmentioning
confidence: 99%